Assessment of dynamic humeral centering in shoulder pain with impingement syndrome: a randomised clinical trial. Issue 9 (29th May 2011) - Beaudreuil, Johann; Lasbleiz, Sandra; Richette, Pascal; Seguin, Gérard; Rastel, Christine; Aout, Mounir; Vicaut, Eric; Cohen-Solal, Martine; Lioté, Frédéric; de Vernejoul, Marie-Christine; Bardin, Thomas; Orcel, Philippe
Abstract : Objectives: Treatment for degenerative rotator cuff disease of the shoulder includes physiotherapy. Dynamic humeral centering (DHC) aims at preventing subacromial impingement, which contributes to the disease. The goal of this study was to assess the effectiveness of DHC. Method: 69 patients with shoulder pain and impingement syndrome were prospectively included in a single-centre randomised trial with a 12-month follow-up. Patients and assessor were blinded to the study hypothesis and treatment, respectively. DHC and non-specific mobilisation as control were performed for 6 weeks, in 15 supervised individual outpatient sessions, and patients performed daily home exercises. The planned primary outcome was the Constant score including subscores for pain, activity, mobility and strength at 3 months. Secondary outcomes were the Constant score and subscores at 12 months, and medication use for pain at 3 and 12 months. Results: The DHC group did not differ from the control group in the total Constant score at 3 months. However, the DHC group showed a higher Constant subscore for pain (12.2 (SD 2.8) vs 9.9 (2.9), least square means difference 2.1, 95% CI 0.7 to 3.5, p=0.004). At 3 months, the DHC group also showed a higher rate of no medication use (96.7% vs 71%, proportional difference 25.7, 95% CI 3.7 to 51.9, p=0.012). There was no other intergroup difference. Conclusions: There was no difference in the total Constant score between DHC and controls. However, pain was improved at 3 months after DHC. The differences found in subscores for pain should be explored in future studies. Trial registration clinicaltrials.gov Identifier: NCT 01022775.